The ingredients of us : a novel - Gold, Jennifer (Lake Union Publishing, 2019)
From debut author Jennifer Gold comes a delicious novel about the sweet and sour ingredients of life and love. Elle, an accomplished baker, has a recipe for every event in her life. But when she discovers her husband's infidelity, she doesn't know what to make of it. Jam, maybe? Definitely jam. Fed up with the stale crumbs of her marriage, Elle revisits past recipes and the events that inspired them. A recipe for scones reminds her of her father's death, cinnamon rolls signify the problematic courtship with her husband, and a batch of chocolate cookies casts Elle in a less-than-flattering light. Looking back, Elle soon realizes that some ingredients were missing all along. After confronting her husband, Elle indulges her sweet tooth in other ways, including a rebound that just leaves her more confused. As secrets from the past collide with the conflicts of the present, Elle struggles to manage her bakery business and maintain the relationships most important to her. In piecing her life back together, will Elle learn to take the bitter with the sweet?